(untitled) (Delta Medical College Journal, 2015)
Background: Gingivitis is one of the common diseases in Bangladesh and a public health problem also. Broadly factors of two categories are responsible for the occurrence of gingivitis: anatomical and behavioral. Few physiological factors also have influence. In Bangladesh we have no national health survey on periodontal condition. Objective: The aim of this study was to find out the factors affecting gingivitis among patients of 15 to 40 years of age attending in a tertiary care hospital in Dhaka city. Materials and method: This was a cross sectional study and purposive sampling method was used. Total 200 samples were taken who fulfilled the inclusion criteria by pretested structured questionnaire in outpatient department (OPD) of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Results: The mean(±SD) age of respondents was 27±5 years. Dietary factors responsible for gingivitis were sweets (80%), followed by fast food (14%). Regarding behavioral factors, smoking (48%), tobacco using (8%) and betel nuts chewing (28%) influenced gingivitis. Most of the respondents (89%) were suffering from gingivitis for at least one year and gum bleeding was documented in 99% of respondents. Conclusion: Dietary and behavioral patterns were found to be responsible for gingivitis. DOI: http://dx.doi.org/10.3329/dmcj.v3i1.22233 Delta Med Col J. Jan 2015; 3(1): 09-12